Blueprint for Success in College and Career - Dillon, Dave (Open textbook library., 2018)
Blueprint for Success in College and Career is a remix of four previously existing OER (Open Educational Resources): A Different Road To College: A Guide For Transitioning To College For Non-traditional Students by Alise Lamoreaux, How to Learn Like a Pro! by Phyllis Nissila, Foundations of Academic Success: Words of Wisdom, edited by Thomas Priester, College Success, provided by Lumen Learning, and one previously copyrighted textbook with content that is now openly licensed: Blueprint for Success in College: Indispensable Study Skills and Time Management Strategies by Dave Dillon. A free OER, (Open Educational Resource), Blueprint for Success in College and Career is a students' guide for classroom and career success. This text, designed to show how to be successful in college and in career preparation focuses on study skills, time management, career exploration, health, and financial literacy.